GUESSING GAME TECHNIQUE IN IMPROVING ENGLISH VOCABULARY MASTERY - Elvi Tamdang; Rizka Indahyanti; Sitti Nurjannah (ADHILINGUA: Journal of Language Education, Lilnguistics and Literature, 2024)
The objective of the research is to explere the guessing game in English vocabulary mastery and to Find Out whether the Use of Guessing Game Techniques is Effective or Not to Improve the English Vocabulary Mastery of the seventh-grade students at SMPN 2 Tual. This research used Classroom Action Research by implementing the Kemmis and MC Taggart design which were consisted of in two cycles. Each cycle consisted of planning, action, observation, and reflection. The object of this research was 54 students in the seventh grade in SMP N 2 Tual, in the Academic Year 2023. The research instrument was a vocabulary test 20 questions multiple choice. The result of this research shows that there was a diffirent improvement in the students' vocabulary mastery in cycle I and cycle II. The student's average score increased significantly. In cycle 1 the students' average score was 72.22 and in cycle 2 it was 89.53. Meaning that the average score obtained by students in the first and second cycle tests is good effective in improving English vocabulary mastery using guessing game technique.